Evaluation of renal function when using dexamethasone therapy in Patients with Covid-19 in Najaf City - Hanan Diekan Abbas; Ahmed Hassan Kudhair (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: The COVID-19 is the one of the most reason that induce the renal problems and could even attack so many organs that might ends with increase the mortality and morbidity rate in the worldwide. One of its common cases is the chronic renal impairment that may be worse and increase the death rate in complete impair renal function. On the other hand the treatment or restoring of the renal abnormality could be occurred in hospital monitoring with a steroid treatment. A regular steroid intake with assessment of renal function base on a urea, creatinine and glucose levels is a good road path to improve the renal function and so shorten the time required for the patient to stay in the hospital. Aim: to predict if the steroid treatment (dexamethasone) could improve the renal function and facilitate the curing rate of the patients. Materials and Method: a case control study was conducted from sixty individuals, one half take the dexamethasone and suffer from COVID with the renal impairment and the other thirty patient was also have the COVID and renal abnormality but without this steroid drug, the blood sample and serum glucose, creatinine and urea measurement was performed. Results: data showed that the level of urea, creatinine and glucose concentrations is lower in those COVID patient with renal abnormalities and take a steroid treatment compared to those didn’t take the course of this drug. Conclusion: steroid treatment is one of the drugs that might improve the case of the patient and might participate in faster the curing rate of the patient and resorting the renal function to the normal level.